Early outcome of permanent pacemaker implantation - Monib, Abdul Khaliq; Nepal, Rajesh; Dhungana, Sahadev; Bista, Madhav; Ghimire, Rakshya (Journal of Nobel Medical College, 2018)
Background: Permanent pacemaker implantation (PPI) is considered the most effective and safe procedure for treatment of symptomatic bradyarrythmia. In this study we evaluated incidence of intraoperative and early postoperative (three month) outcome of PPI in our center. Method: This is a cross sectional study carried out over a period twenty months between Jan 2017 and August 2018. All patients undergoing PPI at Nobel Medical College were enrolled in the study. Details of demographic data, medical history, hardware used and complications were recorded. Prospective follow up was done in outpatient department upto three months. Result: A total of seventy-six patients were enrolled in the study. Fifty-one (67%) were male and twenty-five (33%) were female. Ninety percent of the patient was above the age of sixty-five years. Fifty-five (71%) received single chamber and twenty-one (28%) received dual chamber pacemaker. Majority of the patient (87%) had a diagnosis of complete heart block. There was no mortality unto 3 months. Majority (92%) of the patient had no complications at all. Two patients had pocket site infection. Lead dislodgment was noted in three patients. Lead perforation and acute temponade occurred during intraoperative period in one case, which was successfully managed by pericardiocentesis. Conclusion: In summary permanent pacemaker implantation was effective and relatively safe procedure in our center with no mortality.